1995
DOI: 10.1007/bf01744486
|View full text |Cite
|
Sign up to set email alerts
|

Transesophageal echocardiographically detected atherosclerotic aortic debris in a patient with systemic embolism following coronary angiography

Abstract: Transesophageal echocardiography (TEE) has enabled detection of the cardiac source of systemic emboli. We report the case of a patient who manifested systemic, multiple embolization in the kidney, skin, and upper gastrointestinal tract following coronary angiography. TEE allowed visualization of the atherosclerotic debris in the thoracic aorta. The clinical picture of the patient was consistent with that of cholesterol embolism. We recommend that patients with extensive atherosclerotic disease should undergo T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1996
1996
2005
2005

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 6 publications
0
4
0
Order By: Relevance
“…Ribakove and colleagues [33] found similar results, demonstrating that intraoperative clinical evaluation of aortic artheromatous disease by surgical palpation alone is not predictive of embolic stroke. Other observations revealed that TOE may demonstrate atheromatous plaques of the aortic arch involved in cholesterol embolization [36,37] and so detect patients with a high risk of CCE before surgery. Wareing and colleagues [38] have proposed performing ascending aortic replacement or carotid endarterectomy to decrease the stroke rate after cardiac surgery in patients in whom atheromatous plaques were discovered by intraoperative ultrasonic scanning.…”
Section: Discussionmentioning
confidence: 99%
“…Ribakove and colleagues [33] found similar results, demonstrating that intraoperative clinical evaluation of aortic artheromatous disease by surgical palpation alone is not predictive of embolic stroke. Other observations revealed that TOE may demonstrate atheromatous plaques of the aortic arch involved in cholesterol embolization [36,37] and so detect patients with a high risk of CCE before surgery. Wareing and colleagues [38] have proposed performing ascending aortic replacement or carotid endarterectomy to decrease the stroke rate after cardiac surgery in patients in whom atheromatous plaques were discovered by intraoperative ultrasonic scanning.…”
Section: Discussionmentioning
confidence: 99%
“…1 in page 1061 in the last issue). Sato et al (13) reported a patient who manifested multiple emboli in the kidney, skin and upper gastrointestinal tract following coronary angiography. In that case, transesophageal echocardiography enabled visualization of the atherosclerotic debris in the thoracic aorta.…”
Section: Cholesterol Embolization Syndrome: How Tomentioning
confidence: 99%
“…In that case, transesophageal echocardiography enabled visualization of the atherosclerotic debris in the thoracic aorta. To protect against cholesterol embolization, they recommended that patients with extensive atherosclerotic disease undergo transesophageal echocardiography before cardiac catheterization or other invasive procedures involving the aorta (13). In addition, Duda et al (14) carried out an interesting study to determine whether the routine use of intraoperative surface aortic ultrasonography would reduce the stroke rate among patients undergoing coronary artery bypass graft surgery.…”
Section: Cholesterol Embolization Syndrome: How Tomentioning
confidence: 99%
“…Penetrating mobile semi-occlusive atheroma of the aorta detected by transoesophageal echocardiography has been demonstrated in a number of cases (fig2). 3 4 This pattern of atheroma is an unusual finding and it appears to be a marker of severe widespread atheromatous disease. Further studies into the relation between this pattern of atheromatous aortic disease and the cholesterol emboli syndrome are currently in progress.…”
mentioning
confidence: 96%